Diversity of thermal ecotypes and potential pathotypes of Bacillus thuringiensis soil isolates. Issue 2 (11th April 2013) - Swiecicka, Izabela; Bartoszewicz, Marek; Kasulyte‐Creasey, Daiva; Drewnowska, Justyna M.; Murawska, Emilia; Yernazarova, Aliya; Lukaszuk, Edyta; Mahillon, Jacques
Abstract: Ecological diversification of Bacillus thuringiensis soil isolates was examined to determine whether bacteria adapted to grow at low temperature and/or potentially pathogenic correspond to genetically distinct lineages. Altogether, nine phylogenetic lineages were found among bacilli originating from North‐Eastern Poland ( n = 24) and Lithuania ( n = 25) using multi‐locus sequence typing. This clustering was chiefly confirmed by pulsed‐field gel electrophoresis. One third of the bacilli were found to be psychrotolerant, which strongly supports the hypothesis of the existence of thermal ecotypes among B. thuringiensis . PCR screening was also performed to detect potential enterotoxin genes and Bacillus anthracis pXO1‐ and pXO2‐like replicons. The cytK ‐positive isolates (22%) were significantly associated with two phylogenetic lineages (potential CytK pathotypes), whereas there was no correlation between phylogenetic grouping and the presence of the potential tripartite enterotoxin pathotypes (86% of strains). A statistically significant association between phylogenetic lineages and ecologic properties was found with regard to the cry1 ‐positive Lithuanian isolates, while the cry genes in Polish isolates and the pXO1‐ and pXO2 replicon‐like elements showed scattered distribution across phylogenetic lineages. Our results support the hypothesis that B. thuringiensis comprises strains belonging to different phylogenetic lineages, which exhibit specific ecological properties.